Results of the qualification test campaign of a Pulsed Plasma Thruster for Cubesat Propulsion (PPTCUP). (April 2016) - Ciaralli, S.; Coletti, M.; Gabriel, S.B.
Abstract: Pulsed Plasma Thruster for Cubesat Propulsion (PPTCUP) is an ablative pulsed plasma thruster designed with the aim of providing translational and orbital control to Cubesat platforms. The qualification model presented in this paper has been developed by Mars Space Ltd, Clyde Space Ltd and the University of Southampton to produce a versatile "stand-alone" module that can be bolted on the Cubesat structure, allowing the orbital control along the X or Y -axis of the satellite. An extensive and complete test campaign to qualify the unit for space flight, which includes electromagnetic compatibility (EMC) characterization, thermal cycling and mechanical tests, has been performed according to the NASA GEVS procedures. PPTCUP is characterized by an averaged specific impulse of 655±58 s and a deliverable total impulse of 48.2±4.2 Ns. Finally, it has been found that the unit is compliant with the EMC requirements and can successfully withstand the thermal and mechanical loads typical of a Cubesat space mission. Highlights: We have designed and manufactured a PPT for Cubesat applications. We are running an extensive test campaign to qualify the system for space flight. Mechanical, thermal cycling and EMC tests have been successfully completed. The device will be the first fully qualified PPT for Cubesat applications.